AYAH DALAM KARYA SENI ILUSTRASI REALIS - Violin Nabilla Guve, Ir. Drs. Heldi, M.Si., Ph.D., Drs. Wisdiarman, M.Pd. (Serupa The Journal of Art Education, 2018)
The purpose of this final project is to visualize the importance of father’s role for his children. The idea of creating this project is to visualize the father’s role for his children in the project of realist style illustration. In the procces of creating this final project, there are five stages: they are preparation stage, elaboration stage, synthesis stage, concept of realization phase, and completion phase, The titles of the result of the visualization in this realist illustration is “Father in Realist illustration Art”. The results of the visualization in this illustration work are 10 works with the title: (1) Eyes; (2) Story Tme; (3) Hope; (4) RidingLesson; (5) Sunday Talks; (6) Prayer; (7) Grazie Papa; (8) My Second Mom; (10) My Best FriendKeywords : Father, Art, Realism Illustration